2020
DOI: 10.1136/bmjopen-2020-043312
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions and experiences of the public regarding the COVID-19 pandemic in Nepal: a qualitative study using phenomenological analysis

Abstract: ObjectivesPerceptions of people regarding COVID-19 influences their health behaviour in terms of seeking public health services. This helps the government in planning appropriate public health strategies. Therefore, this study intends to explore the perceptions of people towards COVID-19 and their experiences during the pandemic in Nepal.Design, setting and participantsThis qualitative study was conducted among the public in Kathmandu, Kanchanpur, Bajura and Jhapa districts of Nepal. Eight focus group discussi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
62
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 44 publications
(71 citation statements)
references
References 43 publications
6
62
0
3
Order By: Relevance
“…Our study highlighted that alterations in the individuals' working environments, reduced social (in-person) interactions, and uncertainty about their health and the economy during the MCO had a negative psychological impact on the participants. These findings are similar to those reported in the United Kingdom and Nepal, where physical distancing and isolation policies during the COVID-19 pandemic had adverse effects on the public's psychological and emotional state because of the lack of in-person social interactions, loss of income, and lifestyle changes [5,46]. Another study in Malaysia reported that two-thirds of respondents suffered from moderate-to-severe anxiety during the early phase of the pandemic because of the perception of high severity and susceptibility to COVID-19 [47].…”
Section: Discussionsupporting
confidence: 86%
“…Our study highlighted that alterations in the individuals' working environments, reduced social (in-person) interactions, and uncertainty about their health and the economy during the MCO had a negative psychological impact on the participants. These findings are similar to those reported in the United Kingdom and Nepal, where physical distancing and isolation policies during the COVID-19 pandemic had adverse effects on the public's psychological and emotional state because of the lack of in-person social interactions, loss of income, and lifestyle changes [5,46]. Another study in Malaysia reported that two-thirds of respondents suffered from moderate-to-severe anxiety during the early phase of the pandemic because of the perception of high severity and susceptibility to COVID-19 [47].…”
Section: Discussionsupporting
confidence: 86%
“…This feeling of financial strain and suffering was strongest among daily wage workers, which was also found to be true in Nepal [ 11 ]. Our participants also expressed feelings of fear and social isolation that were also similar to those expressed in Nepal and the UK [ 9 , 11 ], although many rural villagers in Nepal still reported social interactions with neighbors, whereas most rural villagers in our study in India reported that those types of interactions had mostly stopped as everyone was following precautions and afraid of getting the virus. Finally, we found gendered differences in perceptions related to changes in daily life in our study area, with almost all men describing large changes in their daily life and social interactions whereas about a third of women caregivers described little change because they mostly stayed at home even before the lockdowns, likely due to few being employed outside the home and gendered restrictions on social interactions that existed prior to the pandemic.…”
Section: Discussionmentioning
confidence: 81%
“…Takashima et al [ 10 ] used focus groups to understand the perceptions of older adults in Japan in a later stage of the pandemic (July to August 2020) regarding how COVID-19 restricted their daily lives, and generally found little change in their daily personal lives. Bhatt et al [ 11 ] conducted focus groups with adults in Nepal from March to June 2020 to explore perceptions and experiences with COVID-19 and found that there was generally a good understanding about COVID-19 and preventative measures, but varied experiences regarding economic loss and social isolation, including differing experiences in urban and rural areas. These studies offer some overlapping themes and provide a glimpse of the general public’s perceptions and experiences during COVID-19, however many experiences varied across locations and may not be applicable to rural India, which has high levels of poverty and a large informal workforce, and was undergoing the mass return of migrants to rural villages during unprecedented lockdown restrictions.…”
Section: Introductionmentioning
confidence: 99%
“…20 Similarly, a qualitative study of different districts of Nepal found that participants knew that using a mask, washing hands or using sanitizer, and maintaining social distance will help in preventing the spread of COVID-19. 21 Three fourth of the students 290(75.9%) in this study believed that COVID-19 will finally be successfully controlled in Nepal. Likewise, 313(81.9%) of people of Birgunj, Nepal with a medical background, also believed that.…”
Section: Resultsmentioning
confidence: 65%